Advancements in Embedded Neurorehabilitation: Integrating Robotics, Artificial Intelligence, and Virtual Reality for Upper Limb Recovery in Children with Cerebral Palsy - Mohammed Elsaeh (AlQalam Journal of Medical and Applied Sciences, 2026)
Cerebral palsy (CP) remains one of the most common motor disabilities in childhood, often leading to significant impairments in upper limb function that affect activities of daily living (ADLs). This study introduces an innovative embedded neurorehabilitation system that synergistically combines robotics, artificial intelligence (AI), and virtual reality (VR) to target elbow rehabilitation in children with CP. Two male participants, aged 8 and 14 years, underwent an 8-week intervention protocol at Barak General Hospital (BGH) and Wadi Alshatti University (WAU), consisting of 5 sessions per week, each lasting 70 minutes. The system facilitated personalized, adaptive therapy through real-time AI-driven adjustments and immersive VR environments. Pre- and post-intervention assessments demonstrated remarkable improvements: both children achieved full restoration of elbow range of motion (ROM) and regained ADL capabilities, as measured by standardized tools such as the Modified Ashworth Scale (MAS), Goniometry for ROM, and the Pediatric Evaluation of Disability Inventory (PEDI). These findings underscore the potential of integrated technologies in enhancing neuroplasticity and functional outcomes in pediatric CP populations. Limitations include the small sample size, warranting larger-scale trials. This work paves the way for scalable, home-based neurorehabilitation solutions.